MARKETING STRATEGY OF JAWA RANDU GOAT Case Study in Raja Kambing Pengasinan, Depok Regency, West Java Province - R., Fazrulsyah; Putri, B.R.T.; Suarta, I G. (Jurnal Peternakan Tropika; Vol 12 No 1 (2024): Vol. 12 No. 1 Tahun 2024; January - February, 2024)
This study aims to analyze the internal and external environmental factors that influence the marketing strategy of Raja Kambing Pengasinan, Kab. Depok, West Java Province. This research is a case study conducted in Raja Kambing Pengasinan, Kab. Depok, West Java Province. In this study we use 43 peoples consisting of 30 consumers of Raja Kambing Pengasinan, Depok Regency, West Java Province, 10 cusumers from other goat’s farmers, 3 experts (owner, manager), and external (department of food security, agriculture and fisheries, loyality customer) who have good experience in goat farming in Depok Regency. Sources of data used are primary data and secondary data. Data was collected through observation, in-depth interviews and interviews using questionnaires. There are 4 analyzes used in this study namely, 1) internal factor evaluation and external factor evaluation; 2) Internal External matrix used to determine business position; 3) SWOT analysis is used to develop alternative marketing strategies for Raja Kambing Pengasinan, Depok Regency, West Java Province, 4) Quantitive strategic planning matrix. The results of this study show that alternative strategies Raja Kambing Pengasinan. . The Priority strategy is to create marketing promotion to the wider community by placing advertisements on digital media/brochures/posters with TAS value 3.76.